Pengembangan Modul AJar Pendidikan Pancasila Berbasis PBL Untuk Meningkatkan Keterampilan Kolaborasi Siswa kelas V SD - Cicilia Novita Ayundasari Poto; Rusmawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Collaborative skills are important skills that elementary school students need to have because they play a significant role in supporting learning success, especially in group activities that require communication, cooperation, and joint problem solving. In reality, students' collaborative skills are still not optimally developed. This study aims to develop a PBL-based Pancasila Education teaching module that can improve the collaboration skills of fifth-grade elementary school students. The method used is Research and Development with the ADDIE development model. The development process begins with a needs analysis, followed by the design and development of teaching modules, implementation in learning activities, and evaluation to determine the feasibility and effectiveness of the product. The results of the study indicate that the PBL-based Pancasila Education teaching module developed is able to encourage students to actively collaborate. This teaching module is effective for use as teaching material and has the potential to improve the collaboration skills of fifth-grade elementary school students.